Pengaruh Interval Penyadapan Terhadap Motilitas Dan Abnormalitas Spermatozoa Pada Ayam Sentul - Nursabani, Agung Mohamad; Saleh, Dadang Mulyadi; Mugiyono, Sigit (ANGON: Journal of Animal Science and Technology, 2020)
Background. The precious study, entitled "the effect of collectinging intervals on motility and abnormality of spermatozoa in sentul roosters", examines the comparison of collecting frequencies to motility and abnormalities of centimeter spermatozoa increases the activation of selected frequencies to facilitate the motility and abnormality of good spermatozoa. It was carried out on February 23, 2018 to March 29, 2018 at the Gemah Ripah Ranch managed in Sinekung Village, Depok Hamlet, RT 02 RW 04, Sukajadi Village, Sadananya District, Ciamis Regency, West Java Province. Materials and methods. This Research used twenty four Sentul roaster. The research method used was an experimental method with Completely Randomized Design (CRD) with 3 preparations, and 8 replications. As a treatment was Frequency of semen collection (P) consist of P1= once every 3 days; P2= once every 6 days; and P3= once every 9 days. Each experimental unit consisted of 8 Sentul Roosters and repeated 3 times so there were 24 sentul rooster in total. The measured variables discussed were motility and abnormality of spermatozoa. Results. The results showed that the motility values of P1, P2, P3, respectively were 87.70%; 88.13%; 88.34% and abnormalities 9.41%; 9.26%; 9.50%. The result showed F count less than F table 0,05 means hipotesis is rejected. The results of the analysis show the insemination interval 3, 6, and 9 days didi not affected spermatozoa motilities and abnormalities. Conclusion. In conclusion, inseminiation interval 3, 6, and 9 days showed good spermatozoa motility and abnormalities. For the inseminiation interval 3, 6, and 9 days showed the not affected to spermatozoa motility and abnormalities of chickhen sentul.